Bioaccessibility of arsenic and cadmium assessed for in vitro bioaccessibility in spiked soils and their interaction during the Unified BARGE Method (UBM) extraction. (March 2016) - Xia, Qing; Peng, Cheng; Lamb, Dane; Mallavarapu, Megharaj; Naidu, Ravi; Ng, Jack C.
Abstract: Recent decades have seen a growing popularity of in vitro bioaccessibility being utilised as a screening tool in human health risk assessment. However the existing bioaccessibility studies only focus on single contaminant. Considering human are likely to ingest multi-contaminants, these contaminants could interact within human gastrointestinal tract which may lead to an increase or decrease in bioaccessibility. In this study, seven different types of soil were spiked with arsenic (As) or cadmium (Cd) and aged for one year. The effects of soil properties on the bioaccessibility were examined. Moreover, the interaction between As and Cd in simulated human digestive system was studied by mixing As-spiked soil with Cd-spiked soil of the same type during bioaccessibility test. Results shows the bioaccessibility of As ranged from 40 ± 2.8 to 95 ± 1.3% in the gastric phase and 16 ± 2.0 to 96 ± 0.8% in the intestinal phase whilst a significant difference was observed between Cd gastric bioaccessibility (72 ± 4.3 to 99 ± 0.8%) and intestinal bioaccessibility (6.2 ± 0.3 to 45 ± 2.7%). Organic carbon, iron oxide and aluminium oxide were key parameters influencing the bioaccessibility of As (gastric and intestinal phases) and Cd (intestinal phase). No interactions between As and Cd during bioaccessibility test were observed in any soils, which indicates As and Cd may age independently and did not interact while being solubilised during bioaccessibility test. Thus additive effect may be proposed when estimating the bioaccessibility of mixtures of independently-aged As and Cd in soils. Highlights: Organic carbon, iron oxide and aluminum oxide can influence As/Cd bioaccessibility. No interaction between As and Cd during bioaccessibility test occurred in spiked soil. Additive effect may apply to bioaccessibility of independently-aged As and Cd in soil.